Qirā’at dan Tarannum Sebagai Medium Baru Dakwah - Ahsin Sakho Muhammad (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2020)
This paper explore two topics namely qirā’at and tarannum and how they can be used as Islamic dakwah methods in modern era. Among the methods that are quite interesting is through reading the verses of the holy al-Qur’an with tarannum or intone reading the Qur’an. Intoning the reading of the Qur’an will be able to compensate the modern society that is infatuated in music and contemporary art. In line with the influence of globalization, reading the Qur’an experienced a paradigm shift. While in the past, Muslims were accustomed to one type of reading, namely the reading of Imam ‘Āṣim transmitted by Ḥafṣ, then at this time, especially after globalization, the moslims community recognized other readings beside the transmission of Ḥafṣ, namely the reading contained in Qirā’at sevent’s Imams and Qirā’at Ten Imams. Both of these types of reading eventually become quite interesting trends to be learned.